Proceedings of the 1998 American Control Conference. ACC (IEEE Cat. No.98CH36207) 1998
DOI: 10.1109/acc.1998.702983
|View full text |Cite
|
Sign up to set email alerts
|

Detection of common motor bearing faults using frequency-domain vibration signals and a neural network based approach

Abstract: Bearings and their vibration play an important role in the performance of all motor systems. In many cases, the accuracy of the instruments and devices used to monitor and control the motor system is highly dependent on the dynamic performance of the motor bearings. In addition, many problems arising in motor operation are linked to bearing faults. Thus, fault detection of a motor system is inseparably related to the diagnosis of the bearing assembly. This paper presents an approach of using neural networks to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…These basic frequencies defined above can be used to detect the possible faults in bearing or gears. For example, if the defects happen on the raceway of a rolling bearing, the BPOF f or BPIF f will be generated when a roller hits this defective raceway each time [5]. After the bearing defect is detected, some vibration-based features need to be extracted in order to trace the bearing health degradation.…”
Section: Vibration Data Analysismentioning
confidence: 99%
“…These basic frequencies defined above can be used to detect the possible faults in bearing or gears. For example, if the defects happen on the raceway of a rolling bearing, the BPOF f or BPIF f will be generated when a roller hits this defective raceway each time [5]. After the bearing defect is detected, some vibration-based features need to be extracted in order to trace the bearing health degradation.…”
Section: Vibration Data Analysismentioning
confidence: 99%
“…Mo-Yuen Chow et al [16] concluded that the size of training data directly affects the accuracy of the AI system. Bo Li et al (1998) showed that FFT values of a vibration signal spectrum can be used as relevant features of the vibration dataset [17]. The authors of [4,16] proved that optimizing network parameters like learning rate, momentum, and neuron size is important for increasing accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…These features were compared with features computed using the fast Fourier transform (FFT) as a suitable choice for real-time implementation [13]. Li et al introduced a method for motor-bearing fault detection using frequency domain vibration signals and ANN [14]. In this method, the acquired vibration signals in the time domain were converted into the frequency domain using the FFT method.…”
Section: Introductionmentioning
confidence: 99%